2020
DOI: 10.3389/fpls.2020.00174
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Exposure to Ethylene Differentially Affects Senescence in Receptacle and Achene Tissues in Strawberry Fruit

Abstract: Strawberry shelf life is limited, and little is known about the postharvest regulation of senescence in different fruit tissues. Strawberry is classified as a non-climacteric fruit, yet it is known that ethylene affects strawberry ripening. Here the effects of continuous exogenous ethylene (50 µl l −1) were investigated in cold stored strawberry (5°C). The physiological and biochemical responses of ripe strawberry were evaluated across 6 days, together with hormonal profiles of the whole fruit and individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…(2015) also reported that ethylene treatments increased total sugar content in white as well as green detached strawberry fruit. In addition, Tosseti et al. (2020) reported the propensity of ethylene to elicit an accumulation of reducing sugars, together with a concomitant decline in sucrose in cold stored strawberry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2015) also reported that ethylene treatments increased total sugar content in white as well as green detached strawberry fruit. In addition, Tosseti et al. (2020) reported the propensity of ethylene to elicit an accumulation of reducing sugars, together with a concomitant decline in sucrose in cold stored strawberry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used ethylene elicitors or inhibitors have suggested that exogenous ethylene affects some important quality attributes in strawberry fruit, including firmness (Jiang et al, 2001;Villarreal et al, 2008;Villarreal et al, 2009;Villarreal et al, 2016;Elmi et al, 2017), anthocyanin accumulation and phenylalanine ammonia lyase (PAL) activity (Villarreal et al, 2009;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013;Lopes et al, 2015), phenolic compound accumulation (Villarreal et al, 2010;Lopes et al, 2015), organic acids (Merchante et al, 2013;Lopes et al, 2015;Elmi et al, 2017), sugars (Villarreal et al, 2010;Villarreal et al, 2016;Tosetti et al, 2020) and volatile-related genes (Merchante et al, 2013). However, most of these studies have been conducted with immature strawberry fruit following detachment from the plant, which may alter fruit physiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed in the case of other non-climacteric fruit such as strawberry and pepper. They observed ethylene mediated ABA accumulation in strawberry and activation of acyltransferase gene transcription due to overexpression of ethylene regular FveERF (FvH4_5g04470.1) ( Tosetti et al, 2020 ). In pepper ( Capsicum ), ethylene was shown to regulate fruit color, influencing carotenoid biosynthesis positively.…”
Section: Abscisic Acid Mediates the Synthesis Of Ethylene And Crossta...mentioning
confidence: 99%
“…Although ethylene is well known as a key regulator in climacteric fruit ripening ( Liu et al, 2015 ), this gaseous molecule also participates in non-climacteric fruit ripening through its interaction with ABA ( Li et al, 2020 ; Tosetti et al, 2020 ). In postharvest strawberry fruit, ethylene facilitates ABA accumulation in receptacle tissue but does not affect ABA catabolism ( Tosetti et al, 2020 ). Overexpression of FveERF (FvH4_5g04470.1), an ethylene response regulator, activates both acyltransferase (AAT) gene transcription and ester accumulation during strawberry fruit ripening ( Li et al, 2020 ).…”
Section: Central Roles Of Aba In Regulation Of Non-climacteric Fruit mentioning
confidence: 99%